Engineering the oxygen sensing regulation results in an enhanced recombinant human hemoglobin production by Saccharomyces cerevisiae - Martínez, J.; Liu, Lifang; Petranovic, D.; Nielsen, J. (John Wiley and Sons Inc., 2015)
Efficient production of appropriate oxygen carriers for transfusions (blood substitutes or artificial blood) has been pursued for many decades, and to date several strategies have been used, from synthetic polymers to cell-free hemoglobin carriers. The recent advances in the field of metabolic engineering also allowed the generation of different genetically modified organisms for the production of recombinant human hemoglobin. Several studies have showed very promising results using the bacterium Escherichia coli as a production platform, reporting hemoglobin titers above 5% of the total cell protein content. However, there are still certain limitations regarding the protein stability and functionality of the recombinant hemoglobin produced in bacterial systems. In order to overcome these limitations, yeast systems have been proposed as the eukaryal alternative. We recently reported the generation of a set of plasmids to produce functional human hemoglobin in Saccharomyces cerevisiae, with final titers of active hemoglobin exceeding 4% of the total cell protein. In this study, we propose a strategy for further engineering S. cerevisiae by altering the oxygen sensing pathway by deleting the transcription factor HAP1, which resulted in an increase of the final recombinant active hemoglobin titer exceeding 7% of the total cellular protein.